1988
DOI: 10.1111/j.1365-2362.1988.tb02409.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin is a physiological hormonal mediator of fat‐induced inhibition of gastric emptying in man

Abstract: The effect of cholecystokinin-33 on gastric emptying was studied in eight healthy men. The test meal was a firm custard pudding, labelled with 99mTc-Chelex-100 particles. Gastric emptying rate was measured, using a dual-headed gamma camera, and was expressed as the half time of the emptying curve. Plasma cholecystokinin concentrations were determined by radioimmunoassay. Subjects were studied three times: (i) during infusion of saline; during cholecystokinin infusion, (ii) 0.375 IDU kg-1 h-1 and (iii) 0.75 IDU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…In the present study a continuous infusion of CCK8 (250 ng kg-' h-1) had no significant effect on gastric emptying of DM or liquids during the feeding period, and caused only a 14 % slowing of emptying of DM and no effect on emptying of liquids in the 3 h period following the meal. In contrast, this same rate of infusion inhibits emptying of a saline meal in the dog by 62 % (Debas et al 1975) and in the monkey by 92 % (Moran & McHugh, 1982), while in man infusion of CCK8 (30 ng kg-1 h-1) reduced emptying of a water meal by 63 % (Liddle et al 1986), and infusion of CCK33 (the 33 amino acid cholecystokinin peptide) at 0.75 Ivy dog units kg-' h-' (equivalent to 30 ng kg-' h-1 CCK8; Moran & McHugh, 1982) reduces emptying of solids by 57 % (Kleibeuker, Beekhuis, Jansen, Piers & Lamers, 1988). It is evident, therefore, that CCK has a much smaller effect on gastric emptying of both solids and liquids in the pig than in man or dog.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study a continuous infusion of CCK8 (250 ng kg-' h-1) had no significant effect on gastric emptying of DM or liquids during the feeding period, and caused only a 14 % slowing of emptying of DM and no effect on emptying of liquids in the 3 h period following the meal. In contrast, this same rate of infusion inhibits emptying of a saline meal in the dog by 62 % (Debas et al 1975) and in the monkey by 92 % (Moran & McHugh, 1982), while in man infusion of CCK8 (30 ng kg-1 h-1) reduced emptying of a water meal by 63 % (Liddle et al 1986), and infusion of CCK33 (the 33 amino acid cholecystokinin peptide) at 0.75 Ivy dog units kg-' h-' (equivalent to 30 ng kg-' h-1 CCK8; Moran & McHugh, 1982) reduces emptying of solids by 57 % (Kleibeuker, Beekhuis, Jansen, Piers & Lamers, 1988). It is evident, therefore, that CCK has a much smaller effect on gastric emptying of both solids and liquids in the pig than in man or dog.…”
Section: Discussionmentioning
confidence: 99%
“…8,25 Moreover, exogenous administration of CCK dosedependently delays gastric emptying in humans. 21,22 Taken together, these fundings make it clear that CCK is one of several physiological regulators of stomach motility.…”
mentioning
confidence: 92%
“…CCK, on one hand, stimulates gallbladder contraction and pancreatic enzyme secretion and, at the same time, it inhibits gastric emptying. 21,22 When food leaves the stomach and enters the duodenum, CCK is released. The released CCK, in turn, inhibits gastric emptying.…”
mentioning
confidence: 99%
“…Studies measuring the effects of CCK-8 infusion reproducing postprandial bioactive plasma concentrations of the hormone have demonstrated that physiologic concentrations of CCK stimulate gallbladder contraction and delay gastric emptying of liquids (3)(4)(5). However, prior difficulties in measuring circulating concentrations of CCK and the existence of multiple molecular forms of CCK in plasma have limited the interpretation ofthese experiments.…”
Section: Introductionmentioning
confidence: 99%